The Australian experience with switching to extended half‐life factor VIII and IX concentrates: On behalf of the Australian Haemophilia Centre Directors' Organisation. Issue 3 (3rd April 2020) - Brennan, Yvonne; Parikh, Sumit; McRae, Simon; Tran, Huyen
Abstract: Introduction: Extended half‐life (EHL) factor (F) VIII and FIX concentrates became available to selected haemophilia A (HA) and haemophilia B (HB) patients in Australia in March 2018. Aim: To determine factor utilization and bleeding outcomes during the first 6 months of prophylaxis with EHL concentrates, and compare it to the last 6 months of prophylaxis with standard half‐life (SHL) concentrates. Methods: A national, retrospective study was performed using data extracted from the Australian Bleeding Disorders Registry (ABDR). Patients with ≥3 months of EHL exposure were analysed. Results: A total of 129 HA patients (86 Adynovate, 43 Eloctate) and 64 HB (Alprolix) patients were included in the study. For HA, switching to EHL FVIII resulted in decreased injection frequency (3 to 2 per week), improved 'reduced adherence' rates (18% to 7%), decreased median annualized bleeding rate (ABR; 2.0 to 0.0) and increased proportion of patients with zero bleeds (44% to 64%). Actual factor utilization increased by 20 IU/kg/wk on Adynovate and 4 IU/kg/wk on Eloctate. For HB, switching to EHL FIX resulted in decreased injection frequency (2 to 1 per week), improved 'reduced adherence' rates (35% to 11%), decreased median ABR (3.0 to 2.0) and increased proportion of patients with zero bleeds (31% to 46%). Actual factor utilization decreased by 4 IU/kg/wk. There was no clinically significant inhibitor development. Conclusion: Compared to SHL, EHL FVIII resulted in improved bleeding outcomes, albeit at the expense of increased factor utilization. EHL FIX resulted in improved bleeding outcomes despite decreased factor utilization.